Populismo o realidad : el discurso de Donald Trump y los efectos de la inmigración en la economía estadounidense (2017)
This document analyses the legitimacy of president's Donald Trump anti-immigration speech from an economic point of view, studying immigrants' impact on salaries and the unemployment rate in recent years. The econometric model used considers the migrant density in 480 counties in the United States and its effects on the economic variables of study. The results indicate that, after the arrival of immigrants in the country, there is a decrease in the salary of workers in the United States of 0,486%. However, there is no evidence of an immigrants? impact in the unemployment rate.--Tomado del Formato de Documento de Grado.